Assessment of PD-L 1 expression in a tumor improves the accuracy of predicting the risk of regional breast cancer metastases - Zubareva, Evgenia; Senchukova, Marina; Shubin, Dmitriy; Prokofiev, Alexander (Trends in Immunotherapy, 2023)
Background: Improving the accuracy of axillary lymph node (ALN) status assessment and the search for new markers associated with the risk of breast cancer (BC) metastasis continues to be an urgent problem. Aim: To establish the prognostic significance of the expression of PD-L1 in a tumor for assessing the risk of BC metastasis in ALNs. Materials and methods: A retrospective, case‒control cohort study included 158 patients aged 30 to 85 years with newly diagnosed BC. The material for the study was tumor samples obtained by trephine biopsy. The expression of PD-L1 in the tumor was studied on the invasive component of puncture biopsy specimens by immunohistochemistry using PD-L1 polyclonal antibodies. Statistical analysis was performed using Statistica 12.0 software. Receiver operating characteristic (ROC) curves for PD-L1 and Ki67 were constructed to discriminate cases with and without metastases in the ALNs. Univariate and multivariate analyses were performed to establish independent predictors associated with the risk of BC metastasis. A value of p < 0.05 was considered statistically significant. Results: According to the results, independent predictors of a high risk of BC regional metastasis were T2 (OR = 5.81, 95% CI = 1.75–19.35, p = 0.004) and T3-4 (OR = 43.07, 95% CI = 9.31–199.2, p < 0.0001) stages of BC, absence of an intraductal component (OR = 3.68, 95% CI = 1.32–10.33, p = 0.013), presence of lymphovascular invasion (OR = 3.32, 95% CI = 1.34–8.22, p = 0.009), luminal B HER2-positive (OR = 6.82, 95% CI = 1.13–42.26, p = 0.036) and triple negative (OR = 8.52, 95% CI = 1.12–64.89, p = 0.038) molecular biological subtypes of BC, and PD-L1 expression coefficient greater than 1.65 (OR = 6.39, 95% CI = 2.54–16.09, p = 0.0001). Based on the data obtained, an original noninvasive method for assessing a high risk of BC regional metastasis was developed, the sensitivity of which was 80.9%, the specificity - 82.6%, and the accuracy - 85.7%. The area under the curve (AUC) was 0.876 (95% CI = 0.818–0.924, р < 0.0001). Conclusion: The results of the study indicate that the assessment of PD-L1 expression in a tumor can improve the accuracy of predicting the risk of regional BC metastasis.